Spread of the arrow bulleye Priacanthus sagittarius Starnes, 1988 in the Mediterranean Sea - Gökoğlu, Mehmet; Teker, Serkan (Acta Aquatica: Aquatic Sciences Journal, 2018)
Habitat of the family Priacanthidae is tropical and subtropical Atlantic, Indian, and Pacific oceans. The features of the  family members are generally very big eyes, deep bodies, upturned mouth,  and generally reddish color. In the this paper, we report the presence of an arrow bulleye Priancanthus sagittarius in coast of Turkey waters in the Mediterranean Sea. On the 27th December, 2017, a single specimen of P. sagittarius was collected by Mr. Hüseyin Ã‡Ä±nar, captain of the commercial bottom trawler Furkan Reis vessel, off the TaÅŸucu, Mersin (36°07'2.82"N 33°51'6.42"E) Turkey coasts. The specimen of P. sagittarius was collected at a depth of approximatetly 100 m by a bottom trawl net; the mesh size of 22mm. The collected specimen of arrow bulleye P. sagittarius was 255 mm in total length (TL) and 307 g in total weight (TW). The finding of the present study is the first record of specimen along shores of the Mediterranean of Turkey. This record suggests that this species is spread towards to west along in the Mediterranean.